A stable two-coordinate acyclic silylene. - Protchenko, A; Birjkumar, K; Dange, D; Schwarz, A; Vidovic, D; Jones, C; Kaltsoyannis, N; Mountford, P; Aldridge, S (2012)
Simple two-coordinate acyclic silylenes, SiR(2), have hitherto been identified only as transient intermediates or thermally labile species. By making use of the strong σ-donor properties and high steric loading of the B(NDippCH)(2) substituent (Dipp = 2,6-(i)Pr(2)C(6)H(3)), an isolable monomeric species, Si{B(NDippCH)(2)}{N(SiMe(3))Dipp}, can be synthesized which is stable in the solid state up to 130 °C. This silylene species undergoes facile oxidative addition reactions with dihydrogen (at sub-ambient temperatures) and with alkyl C-H bonds, consistent with a low singlet-triplet gap (103.9 kJ mol(-1)), thus demonstrating fundamental modes of reactivity more characteristic of transition metal systems.